Online advertising formats: a creatives viewpoint - Bedwood, Dave (Henry Stewart Talks, 2009)
Too much talk of the format and not enough about the most important thing: what you put inside it, Novelty of technology, Think outside the bubble, How to ruin an online ad in 9 steps
Archived at 2022/04/11